Amanah dalam Pandangan Hadis: Studi Tahkrij, Syarah, dan Tematik - Andini Vansa Dewi; M. Yusuf Wibisono; Wawan Hernawan (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about trust. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about trust in the history of Bukhari no. 6015. The results and discussion of this study indicate that the status of the hadith is authentic with the qualifications of maqbul ma'mul bih for the practice of Islam in improving the quality of one's trust. This study concludes that the hadith narrated by Bukhari no. 6015 is relevant to be used as motivation to improve the quality of trust in a person.